Peran Satreskrim Polda Jabar Dalam Penanggulangan Kejahatan Jalanan - Yusniawati, Tanti (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
The city of Bandung is the capital of West Java Province which is also the center of government and economy of West Java Province, Indonesia. Dubbed as a metropolitan city, the city of Bandung is indicated by high crime and crime, one of which is street crime. Based on this description, the authors aim to analyze the role of the West Java Regional Police Criminal Investigation Unit in dealing with street crime, to analyze the constraints of the West Java Regional Police Criminal Investigation Unit in dealing with street crime, and to analyze the solutions of the West Java Police Criminal Investigation Unit in dealing with street crime. The research method in the form of research specifications used by the author is descriptive analysis, while the approach method used by the author is normative juridical. The research stage conducted by the author is the library stage which consists of primary, secondary, and tertiary materials, then the field stage. The analytical method used by the author is qualitative juridical. The conclusion obtained is that the Satreskim POLDA of West Java plays a major role in preventing and overcoming crime as a preventive function, namely preventing opportunities for crimes to occur, and also as a repressive function, namely uncovering crimes and taking action against criminals with efforts to implement the West Java POLDA strategy in accordance with the direction policy. The obstacles of the West Java POLDA Satreskim in dealing with street crime are the lack of personnel in the field, inadequate facilities and infrastructure, increasing crime rates from year to year and an understanding of the legal basis that members do not understand. And the West Java POLDA Satreskim solution in dealing with crime on the streets is that the West Java Regional Police carry out the Bina Kusuma Lodaya Operation in accordance with the main duties of the Police as stipulated in Article 13 of Law Number 2 of 2002 concerning the Indonesian National Police.